The Role Of Engagement Leadership And Motivation In Pharmaceutical Companies During Pandemic Covid-19 - Krisna Wahyu Nugraha; Noermijati Noermijati; Nanang Suryadi (Jurnal Manajemen Industri dan Logistik, 2022)
This study aimed  to determine the mediating role of employee engagement  in the relationship between transformational leadership and motivation on employee performance. Questionnaires were used to collect data from employees of companies operating in the pharmaceutical sector in Jakarta with  223 respondents. The data analysis used structural equation modeling with Smartpls program. The results of the study showed  that transformational leadership directly can increase employee performance and work engagement. Furthermore, motivation was  able to increase job engagement  but it was  not able to increase performance. Interestingly, employee engagement   had  been able to fully mediate the effect of motivation on employee performance, but it was  unable to mediate the effect of transformational leadership on performance.